DISASTER MANAGEMENT IN ECONOMICALLY WEAKER COUNTRIES AND STRATEGIES FOR INTERNATIONAL ASSISTANCE - Shakhnoza K. Odilova (Modern American Journals, 2025)
This study provides a comprehensive analysis of the effectiveness of disaster aftermath management mechanisms in economically unstable countries and evaluates the efficiency of existing international aid strategies. Using a multifactorial methodology, the research identifies a critical interdependence between institutional capacity, level of economic development, and resilience to natural disasters. It was found that countries with a GDP per capita below USD 3,500 demonstrate, on average, a 67% higher vulnerability to disaster consequences compared to developed nations. An analysis of 243 cases of international aid between 2015 and 2024 revealed structural shortcomings in the coordination of humanitarian efforts, including a misalignment between short-term emergency responses and long-term recovery strategies. An integrated risk management model is proposed, combining pre-disaster vulnerability modeling, resource allocation optimization, and institutional strengthening at the local level. The results have significant theoretical and practical implications for reforming existing humanitarian aid protocols and developing adaptive disaster risk management strategies in economically vulnerable regions.
Keywords: Disaster management, economic vulnerability, humanitarian assistance, institutional capacity, adaptation strategies, climate resilience, international cooperation, systemic risk analysis, multi-level governance, post-conflict reconstruction